SOCIAL SUPPORT AND DECLARED AGGRESSIVE BEHAVIOUR AMONG YOUNG PEOPLE - Lawnik, Anna; Krucińska, Brygida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Aggression is a behaviour seeking to defuse anger or displeasure on people or things. It is an offensive, enemy, and aggressive attitude toward someone. The purpose of the study is to analyse the relationship between perceived social support and aggressive behaviour of students of secondary schools. Field (quantitative) research was conducted among students of third and fourth grades of secondary schools.To collect the data the following research tools were used: Aggression Questionnaire by A. Buss and M. Perry (Amity version), Interpersonal Social Support Scale (Scale ISEL College 48 Version), Author’s questionnaire. The study showed statistically significant correlation for belonging to clusters and sex of respondents, their place of residence and membership in organized social groups. High social support affects low aggressiveness of youth in all subscales: (A- anger, PA- physical aggression, VA- verbal aggression, H - hostility)The highest aggressiveness in the form of A- anger, PA- physical aggression and VA - verbal aggression -  is characteristic of people with an average level of social support. The highest-H hostility is characteristic of responders with the lowest social support.